(untitled) (Research, Society and Development, 2021)
Enteral nutrition (EN) delivers nutrients directly to the gastrointestinal system for individuals who are unable to swallow in acute and chronic phases. Lipids, then, play a significant role and are highly recommended due to their high caloric support that has supplements in enteral diets performed by adding foods that are rich sources of essential fatty acids, such as polyunsaturated fatty acids (PGPIs), linoleic, and alfa linolenic, since both AGPIs are associated with numerous health benefits, helping patients’ rapid recovery. For the beginning of nutritional therapy, a qualified professional in the health area, who understands the patient’s needs, is essential. Therefore, the aim of this review was to discuss the scientific evidence on the lipid nutritional composition of enteral diets. The research was conducted with publications on the lipid composition of enteral diets used at home, indexed in the electronic databases PubMed (US National Library of Medicine), Scientific Electronic Library Online Brazil (SciELO), Web of Science and Portal Capes. The results allow health professionals to define the type of enteral nutrition suitable for the treatment of their patients, aiming at the synthesis or maintenance of health.